2017
DOI: 10.7455/ijfs/6.2.2017.a10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical, milling and cooking properties of four new rice (Oryza sativa L.) varieties in Nigeria

Abstract: This comparative study investigated some physical, milling and cooking properties of four new rice varieties (FARO 44, FARO 52, FARO 60 and FARO 61) in Nigeria. The varieties were processed into white rice and their properties analyzed separately using standard procedures. Results showed that paddy length, paddy-length-to-width-ratio, equivalent diameter, sphericity, grain volume, aspect ratio, thousand paddy grain weight, milled rice length, milled rice width, milled rice length to width ratio, milling recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…The extraction rate had a negative correlation with the percent of kernel breakage ( Table 2 and 3); the higher extraction rates, the lesser kernel breakage detected. The extraction rate range of the two varieties with different moisture content was between 44% and 63%, and it was higher than the extraction rate mentioned by Sanusi et al (2017), which was between 13% and 48% for four different varieties. While in the Rather et al (2016) study the head rice percentage was between 66% and 68%.…”
Section: Physical Propertiescontrasting
confidence: 55%
“…The extraction rate had a negative correlation with the percent of kernel breakage ( Table 2 and 3); the higher extraction rates, the lesser kernel breakage detected. The extraction rate range of the two varieties with different moisture content was between 44% and 63%, and it was higher than the extraction rate mentioned by Sanusi et al (2017), which was between 13% and 48% for four different varieties. While in the Rather et al (2016) study the head rice percentage was between 66% and 68%.…”
Section: Physical Propertiescontrasting
confidence: 55%
“…The length and breadth ratio along with the amylose content of the grains exhibited a positive correlation (r = .95) with the elongation ratio of the cooked rice. The investigated results presented in Table 10 are in coherence with the outcomes reported by Sanusi et al (2017) who evaluated the elongation ratios of 12 brown rice cultivars native to Nigeria. Comparable outcomes for the elongation ratio of south Indian rice cultivars were reported by Nikitha and Natarajan (2020).…”
Section: Kernel Elongation Ratiosupporting
confidence: 83%
“…It was observed that the rice varieties manifesting higher values of equivalent diameter and geometric mean diameter also demonstrated greater values for thousand kernel weight. Thousand kernel weight of brown rice was found to be lesser than paddy for each respective cultivar because the process of dehusking not only removes the husk from the kernel, but also results in some breakages (Sanusi et al, 2017). The investigated results were found to be in parallel hyphenation with the outcomes reported by Bhat and Riar (2016).…”
Section: Gravimetric Characteristicsmentioning
confidence: 60%
See 1 more Smart Citation
“…The sphericity values of raw, rough rice fall within the range of 0.32-1, as Mohsenin (1986) reported for most agricultural materials. Paddy grains with small sphericity will likely be more challenging to roll freely on a flat surface area (Sanusi et al, 2017). In the current study, Malaysian and Thai varieties present 38.72% and 38.87% sphericity, respectively.…”
Section: Physical Properties Of Malaysian Rice and Thai Ricementioning
confidence: 64%